2017
DOI: 10.1002/jclp.22446
|View full text |Cite
|
Sign up to set email alerts
|

The Journey Through and Beyond Mental Health Services in the United Kingdom: A Typology of Parents’ Ways of Managing the Crisis of Their Teenage Child's Depression

Abstract: Objective Depression is a common mental illness experienced by young people. Yet we know little about how their parents manage their symptoms at home, and how parents may experience their treatment at child and adolescent mental health services (CAMHS). Thus, the aim of our study was to create a typology of parents’ experiences over a 2‐year period, beginning with their teenage child's referral to CAMHS in the United Kingdom. Method A total of 85 semistructured interviews were conducted with one or both parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Step 6: Credibility Checks In line with other research (44,45,48,49), credibility checks were carried out to make certain that the ideal types and descriptions clearly reflected the data, and that each case was categorized under the most suitable type. To ensure this process was rigorous, it involved the input of three co-authors, including the first author and an independent co-judge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 6: Credibility Checks In line with other research (44,45,48,49), credibility checks were carried out to make certain that the ideal types and descriptions clearly reflected the data, and that each case was categorized under the most suitable type. To ensure this process was rigorous, it involved the input of three co-authors, including the first author and an independent co-judge.…”
Section: Discussionmentioning
confidence: 99%
“…Further, as outlined by Stapley et al ( 49 ) there are limitations to using ideal type analysis as a form of data analysis, including the reality that smaller details of participant interviews may be omitted in the process of analysis. This is because condensing large amounts of detailed interview data is necessary in the early stages of analysis to create brief case reconstructions that reflect the aim of the study.…”
Section: Limitationsmentioning
confidence: 99%
“…It may be that those in primary mental health care or education may benefit from further training or resources to allow them to respond to young people presenting with mental health difficulties and to consider parents in their assessments. Stapley et al (2017) identified three distinct patterns of parental experiences of their adolescent's journey through CAMHS services, and suggested that services need to adapt their working approaches with families in order to support these parents in the most appropriate ways. Clinicians and service managers need to work towards providing clear guidance and timely care for young people as per government guidelines (Department of Health 2015).…”
Section: Limitationsmentioning
confidence: 99%
“…Results showed positive reductions in parent stress and perceived symptom severity. A more recent qualitative study is relevant to filling the literature gap in understanding parent involvement in CAMHS (Stapley, Target, & Midgley, 2017). It explores the experiences of parents of 28 adolescents who are being treated for depression and presents some interesting findings about types of parent patterns of their experience over a 2-year period.…”
Section: Gaps and Limitations Revealed In The Research Literature On mentioning
confidence: 99%